2015
DOI: 10.1002/jbio.201500004
|View full text |Cite
|
Sign up to set email alerts
|

Label‐free in vivo imaging of peripheral nerve by multispectral photoacoustic tomography

Abstract: Unintentional surgical damage to nerves is mainly due to poor visualization of nerve tissue relative to adjacent structures. Multispectral photoacoustic tomography can provide chemical information with specificity and ultrasonic spatial resolution with centimeter imaging depth, making it a potential tool for noninvasive neural imaging. To implement this label‐free imaging approach, a multispectral photoacoustic tomography platform was built. Imaging depth and spatial resolution were characterized. In vivo imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Therefore, whether the negative results of this study are related to the shallow imaging depth of OR‐PAM should be confirmed by additional studies. Photoacoustic computed tomography has promised a greater detection depth , which can be introduced into studies of acupoint sensitization. In addition, the time needed to acquire an image with OR‐PAM is dependent on the imaging range, scanning step and scanning speed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, whether the negative results of this study are related to the shallow imaging depth of OR‐PAM should be confirmed by additional studies. Photoacoustic computed tomography has promised a greater detection depth , which can be introduced into studies of acupoint sensitization. In addition, the time needed to acquire an image with OR‐PAM is dependent on the imaging range, scanning step and scanning speed.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators are already exploring methods for improvement. For example, Li et al demonstrated that surface illumination of tissue can provide an imaging depth of up to 2 mm . This technique is not limited to external surfaces; light is introduced into tissues using an optical fiber, then imaged at the surface with a clinical ultrasound transducer (14‐5 MHz).…”
Section: Paimentioning
confidence: 99%
“…Therefore, PAT can provided useful compositional information that complements current clinical imaging modalities, thus emphasizing the capability of this imaging approach to improve medical care. These characteristics highlight the potential of the technology to be used for a variety of biomedical applications including atherosclerosis [[4], [5], [6], [7], [8], [9]], cancer [[10], [11], [12]], and nerve imaging [13]. …”
Section: Introductionmentioning
confidence: 99%